The Effect of Saffron Supplement on Clinical Outcomes, Inflammatory and Oxidative Markers in Patients With Active Rheumatoid Arthritis. (7th June 2021) - Aryaeian, Naheed; Hamidi, Zahra; Shirani, Fatemeh; Hadidi, Mahsa; Abolghasemi, Jamileh; Moradi, Nariman; Fallah, Soudabeh
Abstract: Objectives: Rheumatoid arthritis (RA) is a systemic autoimmune and inflammatory disease. our study aimed to determine the effect of Saffron supplement on clinical outcomes and metabolic profiles in patients with active RA. Methods: In this randomized double-blind placebo-controlled trial, Sixty-six women older than 18 received 100 mg/day either Saffron supplement in the intervention group ( n = 33) or matched placebo in the placebo group ( n = 33) for a period of 12 weeks. Sixty-one patients remained for the final analysis. No adverse effects were reported by the patients. Results: Saffron supplementation significantly decreased the number of tender and swollen joints, pain intensity based on VAS and disease activity score (DAS28) at the end of the intervention in the Saffron group compared with baseline values ( P < 0.001). Also, there was a significant difference between the two groups after intervention for these variables ( P < 0.001), PGA and ESR were significantly improved after the intervention ( P = 0.002 and P = 0.028 respectively). hs-CRP reduced at the end of the intervention in the Saffron group compared with baseline values ( P = 0.004). TNF-α, IFN-γ, and MDA were decreased and TAC was increased but their differences were not significant ( P > 0.05). Conclusions: According to the results, the saffron supplement could positively and significantly improve clinical outcomes in RA patients. Funding Sources: The present article was supported by Iran University of Medical Sciences grants no. 31, 302. The study was approved by the Ethics committee of Iran University of Medical Sciences (IR.IUMS.REC 1396.9, 411, 323, 005).